1997
DOI: 10.1097/00001756-199711100-00023
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D1-deficient mutant mice do not express the late phase of hippocampal long-term potentiation

Abstract: The possible involvement of the dopamine D1 receptor subtype in mechanisms of long-term potentiation (LTP) of the Schaffer collateral-commissural input of CA1 neurones was investigated using D1-deficient mutant mice. In transversal hippocampus slices from mice lacking the D1 receptor a normal post-tetanic and short-term potentiation could be induced after applying a triple 100 Hz tetanization. However, the potentiated fEPSP in the mutant mice declined to control value about 140 min following tetanization, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 12 publications
2
55
0
1
Order By: Relevance
“…At 100 min, LTP was 121 Ϯ 6% (n ϭ 7) in SCH23390-treated slices and 162 Ϯ 5% in control slices (n ϭ 7, P Ͻ 0.01). Considered together, these results suggest that the activation of D1 receptor is mainly involved in the late maintenance of LTP, which is consistent with the effects of D1 receptor inhibition of Schaffer-collateral LTP in the hippocampal slices (19,20). The D2-type receptor antagonist sulpiride (50 M) had no affect on LTP (Fig.…”
Section: D1 But Not D2 Receptors Are Involved In the Maintenance Ofsupporting
confidence: 86%
“…At 100 min, LTP was 121 Ϯ 6% (n ϭ 7) in SCH23390-treated slices and 162 Ϯ 5% in control slices (n ϭ 7, P Ͻ 0.01). Considered together, these results suggest that the activation of D1 receptor is mainly involved in the late maintenance of LTP, which is consistent with the effects of D1 receptor inhibition of Schaffer-collateral LTP in the hippocampal slices (19,20). The D2-type receptor antagonist sulpiride (50 M) had no affect on LTP (Fig.…”
Section: D1 But Not D2 Receptors Are Involved In the Maintenance Ofsupporting
confidence: 86%
“…In this context, we concluded that D1R plays an important role in detecting spatial novelty encoded by spatial representations of hippocampal place cells, a prerequisite for spatial learning. The present work together with other recent studies (Gasbarri et al, 1996;Matthies et al, 1997;Otmakhova and Lisman, 1996;El-Ghundi et al, 1999;Swanson-Park et al, 1999;Wilkerson and Levin, 1999;Tran et al, 2002Tran et al, , 2005Li et al, 2003;Kentros et al, 2004;Gill and Mizumori, 2006;Stuchlik and Vales, 2006) should help significantly in revealing the mechanisms underlying the involvement of dopamine in learning and memory, from the molecular, to the neuronal, to the behavioral level.…”
Section: Discussionmentioning
confidence: 56%
“…It was found that dopamine D 1 receptor knock-out (D1R-KO) mice had impaired spatial learning and altered spatial activity in the nucleus accumbens (El-Ghundi et al, 1999, Tran et al, 2005. Since dopamine modulates hippocampal synaptic plasticity (Otmakhova and Lisman, 1996;Matthies et al, 1997;Swanson-Park et al, 1999;Li et al, 2003), it is hypothesized that the acquisition of spatial representations in the hippocampus is impaired in D1R-KO mice. The present study tested this hypothesis by comparing place-cell activity in D1R-KO and wild-type (WT) mice in response to spatial cue manipulations in familiar and novel environments.…”
Section: Introductionmentioning
confidence: 99%
“…Also, there are experimental data supporting the existence of dopamine D1/D5 receptor-NMDA receptor interactions involving plastic changes in hippocampal excitatory synaptic transmission. Thus, D1/ D5 receptors appear to play an important role in the hippocampal "late phase" long-term potentiation (L-LTP) (Frey et al 1993;Huang and Kandel 1995;Matthies et al 1997). The present findings show that, in addition to the VTA and the nucleus accumbens (see introduction), the VH is an important locus of interaction between dopamine and glutamate in relation to the control of motor activity.…”
Section: Discussionmentioning
confidence: 99%